1980
DOI: 10.1007/bf00251012
|View full text |Cite
|
Sign up to set email alerts
|

Problems in the use of polycarbonate diffusion chambers for syngeneic pancreatic islet transplantation in rats

Abstract: Islets of Langerhans have been enclosed in polycarbonate diffusion chambers and transplanted intraperitoneally to syngeneic streptozotocin diabetic rats. Direct implantation of 1100--1400 islets in these chambers failed to reverse diabetes during a period of 12 weeks, and viable islet tissue was not recoverable at the end of this period. Islets placed in chambers which had been implanted 3--12 weeks previously similarly failed to lower blood glucose of diabetic recipients, as a result of lack of survival of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

1981
1981
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…The ensheathing reaction is believed to be a major contributing factor to decreases in indwelling device performance; however, the precise mechanisms that cause failure are not known [13][14][15][16][17][18][19][20][21][22][23]. For example, catheters implanted for draining excessive cerebrospinal fluid can be blocked by cellular ingrowth and may require frequent surgical revision [22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ensheathing reaction is believed to be a major contributing factor to decreases in indwelling device performance; however, the precise mechanisms that cause failure are not known [13][14][15][16][17][18][19][20][21][22][23]. For example, catheters implanted for draining excessive cerebrospinal fluid can be blocked by cellular ingrowth and may require frequent surgical revision [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…For example, catheters implanted for draining excessive cerebrospinal fluid can be blocked by cellular ingrowth and may require frequent surgical revision [22,23]. Increases in microelectrode impedance and loss of neuronal recording has been attributed to the encapsulating brain tissue response [13,20,21], and it has been suggested that glial encapsulation may reduce the permeability of microdialysis membranes and cell encapsulation devices [17][18][19]24].…”
Section: Introductionmentioning
confidence: 99%
“…At this time, the amount of insulin recovered and the kinetics have almost fully returned to normal and are not significantly different from those in the control group. This is a rather unexpected finding, since several publications report increasing fibrosis during the first months after implantation [19][20][21][22]. A possible explanation could be changes in, or even degradation of, the membrane material.…”
Section: Discussionmentioning
confidence: 71%
“…The in vivo diffusion barrier will depend partly on the immunoisolating membrane but also on the tissue reaction in the recipient. The development of an avascular foreing body reaction around an implant, a common problem in the fields of both macro-and microencapsulation, will hinder the survival and function of the encapsulated graft, while a well-vascularized surrounding tissue should be favorable [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically a semiporous membrane will exclude cells or molecules able to mediate rejection, while allowing flux of insulin and glucose. The composition, structure and diffusion characteristics of several membranes and chambers and the problems with their use has been assessed by Theodorou et al [239].…”
Section: Prevention Of Rejection By Imrnuno-mechanical Barriersmentioning
confidence: 99%